Detection of intracellular bacterial communities in human urinary tract infection. - David A Rosen (Public Library of Science (PLoS), 2007)
Background Urinary tract infections (UTIs) are one of the most common bacterial infections and are predominantly caused by uropathogenic Escherichia coli (UPEC). While UTIs are typically considered extracellular infections, it has been recently demonstrated that UPEC bind to, invade, and replicate within the murine bladder urothelium to form intracellular bacterial communities (IBCs). These IBCs dissociate and bacteria flux out of bladder facet cells, some with filamentous morphology, and ultimately establish quiescent intracellular reservoirs that can seed recurrent infection. This IBC pathogenic cycle has not yet been investigated in humans. In this study we sought to determine whether evidence of an IBC pathway could be found in urine specimens from women with acute UTI. Methods and findings We collected midstream, clean-catch urine specimens from 80 young healthy women with acute uncomplicated cystitis and 20 asymptomatic women with a history of UTI. Investigators were blinded to culture results and clinical history. Samples were analyzed by light microscopy, immunofluorescence, and electron microscopy for evidence of exfoliated IBCs and filamentous bacteria. Evidence of IBCs was found in 14 of 80 (18%) urines from women with UTI. Filamentous bacteria were found in 33 of 80 (41%) urines from women with UTI. None of the 20 urines from the asymptomatic comparative group showed evidence of IBCs or filaments. Filamentous bacteria were present in all 14 of the urines with IBCs compared to 19 (29%) of 66 samples with no evidence of IBCs (p < 0.001). Of 65 urines from patients with E. coli infections, 14 (22%) had evidence of IBCs and 29 (45%) had filamentous bacteria, while none of the gram-positive infections had IBCs or filamentous bacteria. Conclusions The presence of exfoliated IBCs and filamentous bacteria in the urines of women with acute cystitis suggests that the IBC pathogenic pathway characterized in the murine model may occur in humans. The findings support the occurrence of an intracellular bacterial niche in some women with cystitis that may have important implications for UTI recurrence and treatment.